2014 IEEE Wireless Communications and Networking Conference (WCNC) 2014
DOI: 10.1109/wcnc.2014.6952290
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical successive stream selection for heterogeneous network interference

Abstract: Abstract-This paper presents a hierarchical stream selection approach to deal with the interference in a heterogeneous network where different cell types are coexisting with each other to increase the sum capacity. Due to the variety of the transmit powers between the macro and small cells, interference levels are different. The proposed solution hierarchically selects the strongest streams of each cell with a contribution to the sum rate, while constructing the streams via singular value decomposition (SVD). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…Hierarchical IA has been extended for dense deployments of pico cells by a multi-stage alignment process with a decrease in per user capacity performance [21]. In [22], a stream selection algorithm has been developed for heterogeneous networks such that the interference is handled by an orthogonalization procedure on the hierarchically selected streams in a heterogeneous network that is composed of one pico cell and one macro cell. It has been shown that the DoF can be increased by exploiting the partial connectivity, i.e., by considering a subset of cross-channels between transmitters and receivers in the homogeneous networks [23].…”
Section: Introductionmentioning
confidence: 99%
“…Hierarchical IA has been extended for dense deployments of pico cells by a multi-stage alignment process with a decrease in per user capacity performance [21]. In [22], a stream selection algorithm has been developed for heterogeneous networks such that the interference is handled by an orthogonalization procedure on the hierarchically selected streams in a heterogeneous network that is composed of one pico cell and one macro cell. It has been shown that the DoF can be increased by exploiting the partial connectivity, i.e., by considering a subset of cross-channels between transmitters and receivers in the homogeneous networks [23].…”
Section: Introductionmentioning
confidence: 99%
“…The behavior of ISNSSS algorithm depending on the position of one pico cell is analyzed in [14] by implementing exhaustive stream selection algorithm that searches all possible stream sequences. In the study of [15], ISNSSS algorithm is analyzed for two pico cells without satisfying the constraint given in Equation (6b).…”
Section: Performance Resultsmentioning
confidence: 99%
“…The IA approaches have been extended for cellular networks . Besides, IA has also been studied for heterogeneous networks to handle the problems caused by the coexistence of macro and small cells .…”
Section: Introductionmentioning
confidence: 99%